Letter (copy) : Basque Children - Tewson, Vincent
1941-01-01 038-0036-003 Secretary's HVT/FC/KA/192 Mr. T.M. Ferguson, Dundee and District Union of Jute and Flax Workers, 69/71 Nethergate, Dundee. 1st January 1941 Dear Mr. Ferguson, BASQUE CHILDREN I am in receipt of your letter of the 30th ultimo on the above subject. As you will be aware, the General Council made a special appeal for a fund to help Spain whilst the civil war was in progress in that country. The fund was used to assist the Committee responsible for the care of the Basque children in this country. For eighteen months, however, the money raised has also been used for Spanish seamen, and has long since been exhausted. The General Council maintain their contact with the Basque Children's Committee but have not made any financial grant for some time. The fund is not closed, however, and at intervals contributions are received, particularly in connection with the continued support of Spanish seamen which we have taken on as a direct responsibility. If, however, your union desires to make any grant and to earmark it for Basque children, we would see that the money is used for that purpose. I very much appreciate your enquiry, as it is 292/946/38/36(III)